James and the giant peach - Dahl, Roald, 1916-1990; Blake, Quentin (New York : Puffin Books, 2013)
A young boy escapes from two wicked aunts and embarks on a series of adventures with six giant insects he meets inside a giant peach.
Ages 7 up.
Keywords: Loneliness -- Juvenile fiction; Fantasy fiction